Synthesis and Characterization of Hydrochar and Bio-oil from Hydrothermal Carbonization of Sargassum sp. using Choline Chloride (ChCl) Catalyst - Heri Rustamaji; Tirto Prakoso; Jenny Rizkiana; Hary Devianto; Pramujo Widiatmoko; Guoqing Guan (International Journal of Renewable Energy Development, 2022)
The purpose of this study is to alter the biomass of Sargassum sp. into elective fills and high valuable biomaterials in a hydrothermal process at 200oC for 90 minutes, using ZnCl2 and CaCl2 activating agents, withChClas a catalyst. This method generatedthree primaryoutputs: hydrochar, bio-oil, and gasproducts. ChCl to water ratio varies from 1:3, 1:1, and 3:1. The hydrochar yield improved when the catalyst ratio was increased, but the bio-oil and gas yield declined. The highest hydrochar yields were 76.95, 63.25, and 44.16 percent in ZnCl2, CaCl2, and no activating agent samples, respectively.The porosity analysis observed mesopore structures with the most pore diameters between 3.9-5.2 nm with a surface area between 44.71-55.2. The attribute of interaction between activator and catalyst plays a role in pore formation. The hydrochar products with CaCl2 showed the best thermal stability. From the whole experiment, the optimum hydrochar yield (76.95%), optimum surface area (55.42 m2 g-1), and the increase in carbon content from 21.11 to 37.8% were achieved at the ratio of ChCl to water was three, and the activating agent of ZnCl2. The predominant bio-oil components were hexadecane, hexadecanoic, and 9-octadecenoic acids, with a composition of 51.65, 21.44, and 9.87%, respectively the remaining contained aromatic alkanes and other fatty acids. The findings of this study reported that adding activating agents and catalysts improve hydrochar yield and characteristics of hydrochar and bio-oil products, suggesting the potential of hydrochar as a solid fuel or biomaterial and bio-oil as liquid biofuel